Devolution of donor funded climate change adaptation finance - Per Tidemand (Danish Institute for International Studies (DIIS), 2022)
This working paper analyses the nature of international adaptation finance received in Kenya and Tanzania, with particular emphasis on the extent to which the projects were devolved and thus potentially more responsive to the priorities for climate change adaptation as determined by local governments (LGs) and communities. The analysis is based on the OECD database of projects in the period 2013-2019 with projects selected based on their financial value, measured as 'adaptationrelated development finance'. During this period Tanzania received USD 2.0 billion as adaptation-related development finance, whereas Kenya received USD 3.3 billion. In each country, the research team selected the most valuable projects that together constitute 70% of total adaptation-related development finance in the two countries. A method for analysis of the project documents to measure degree of devolution was developed with three main parameters: (i) the extent to which finance was managed through local government accounts; (ii) the extent to which the projects in the respective national budgets were considered devolved; and (iii) the extent to which funding was discretionary and using of participatory planning arrangements for management of the funds. Given Kenya's greater emphasis on devolution, its fiscal strengths, and the autonomy of its counties, when compared to Tanzanian local governments, it was assumed that adaptation-related development finance would be relatively more devolved in Kenya than Tanzania. However, preliminary analysis suggests otherwise. The analysis also suggests that projects classified by development partners as 'adaptation-related development finance' in several cases exaggerate levels of funding and only contribute marginally to improved local governance of climate adaption activities. This analysis is an initial step of a four-year comparative research programme on the governance of climate change adaptation finance in the two countries. The article raises key issues for future in- depth country and local research.
Keywords: 330; Kenya; Tanzania; climate change; climate change adaptation; donor support